Embracing a new paradigm for temperature sensitivity of soil microbes. (30th March 2020) - Alster, Charlotte J.; von Fischer, Joseph C.; Allison, Steven D.; Treseder, Kathleen K.
Abstract: The temperature sensitivity of soil processes is of major interest, especially in light of climate change. Originally formulated to explain the temperature dependence of chemical reactions, the Arrhenius equation, and related Q10 temperature coefficient, has a long history of application to soil biological processes. However, empirical data indicate that Q10 and Arrhenius model are often poor metrics of temperature sensitivity in soils. In this opinion piece, we aim to (a) review alternative approaches for characterizing temperature sensitivity, focusing on macromolecular rate theory (MMRT); (b) provide strategies and tools for implementing a new temperature sensitivity framework; (c) develop thermal adaptation hypotheses for the MMRT framework; and (d) explore new questions and opportunities stemming from this paradigm shift. Microbial ecologists should consider developing and adopting MMRT as the basis for predicting biological rates as a function of temperature. Improved understanding of temperature sensitivity in soils is particularly pertinent as microbial response to temperature has a large impact on global climate feedbacks. Abstract : In this opinion piece, review alternative approaches to Q10 and Arrhenius for characterizing temperature sensitivity of soil biological processes focusing on macromolecular rate theory (MMRT). We provide strategies and tools for implementing a new temperature sensitivity framework, develop thermal adaptation hypotheses for the MMRT framework, and explore new questions and opportunities stemming from this paradigm shift. Improved understanding of temperature sensitivity in soils is particularly pertinent as microbial response to temperature has a large impact on global climate feedbacks.